TweetTracker: An Analysis Tool for Humanitarian and Disaster Relief - Kumar, Shamanth; Barbier, Geoffrey; Abbasi, Mohammad; Liu, Huan (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Social media is becoming popular as a key source of information on disasters and crisis situations. Humanitarian Aid and Disaster Relief (HADR) respondents can gain valuable insights and situational awareness by monitoring social mediabased feeds. Specifically, the use of microblogs (i.e., Twitter) has been shown to provide new information not otherwise attainable. In this paper, we present a new application designed to help HADR relief organizations to track, analyze, and monitor tweets. The purpose of this tool is to help these first responders gain situational awareness immediately after a disaster or crisis. The tool is capable of monitoring and analyzing location and keyword specific Tweets with nearreal- time trending, data reduction, historical review, and integrated data mining tools. In this paper, we discuss the utility of this tool through a case study on tweets related to the Cholera crisis in Haiti.